\[Стр.\ 66.\]
\[\boxed{\mathbf{9.}}\]
\[\textbf{б)}\ 13\frac{2}{7} \cdot 7 = \left( 13 + \frac{2}{7} \right) \cdot 7 =\]
\[= 13 \cdot 7 + \frac{2}{7} \cdot 7 = 91 + 2 = 93\]
\[\textbf{в)}\ 5\frac{2}{11} \cdot ( - 3) =\]
\[= \left( 5 + \frac{2}{11} \right) \cdot ( - 3) =\]
\[= 5 \cdot ( - 3) + \frac{2}{11} \cdot ( - 3) =\]
\[= - 15 - \frac{6}{11} = - 15\frac{6}{11}\]
\[\textbf{г)}\ 9\frac{1}{7} \cdot ( - 2) = \left( 9 + \frac{1}{7} \right) \cdot ( - 2) =\]
\[= 9 \cdot ( - 2) + \frac{1}{7} \cdot ( - 2) =\]
\[= - 18 - \frac{2}{7} = - 18\frac{2}{7}\]
\[\boxed{\mathbf{10.}}\]
\[\textbf{б)}\ 0,84 \cdot 6 + 0,16 \cdot 6 =\]
\[= 6 \cdot (0,84 + 0,16) = 6 \cdot 1 = 6\]
\[\textbf{в)}\ 0,77 \cdot 23 + 0,77 \cdot 77 =\]
\[= 0,77 \cdot (23 + 77) =\]
\[= 0,77 \cdot 100 = 77\]
\[\textbf{г)}\frac{3}{7} \cdot \frac{4}{17} - \frac{3}{7} \cdot \frac{4}{17} =\]
\[= \frac{4}{17} \cdot \left( \frac{3}{7} - \frac{3}{7} \right) = \frac{4}{17} \cdot 0 = 0\]
\[\textbf{д)}\frac{16}{27} \cdot \left( - \frac{25}{72} \right) + \frac{16}{27} \cdot \left( - \frac{11}{72} \right) =\]
\[= \frac{16}{27} \cdot \left( - \frac{25}{72} - \frac{11}{72} \right) =\]
\[= \frac{16}{27} \cdot \left( - \frac{36}{72} \right) = - \frac{16 \cdot 36}{27 \cdot 72} =\]
\[= - \frac{8}{27}\]
\[\textbf{е)}\frac{19}{20} \cdot \left( \frac{2}{19} - \frac{3}{7} \right) + \frac{19}{20} \cdot \frac{3}{7} =\]
\[= \frac{19}{20} \cdot \left( \frac{2}{19} - \frac{3}{7} + \frac{3}{7} \right) = \frac{19}{20} \cdot \frac{2}{19} =\]
\[= \frac{1}{10}\]
\[= \frac{24}{37} \cdot 0 = 0\]
\[\textbf{з)}\frac{3}{5} \cdot \left( \frac{6}{7} - \frac{5}{3} \right) + \frac{6}{5} \cdot \left( \frac{5}{6} - \frac{3}{7} \right) =\]
\[= \frac{3}{5} \cdot \frac{6}{7} - \frac{3}{5} \cdot \frac{5}{3} + \frac{6}{5} \cdot \frac{5}{6} - \frac{6}{5} \cdot \frac{3}{7} =\]
\[= \frac{18}{35} - 1 + 1 - \frac{18}{35} = 0\]
\[= - \frac{11 \cdot 3}{13 \cdot 7} + \frac{1}{2} + \frac{11 \cdot 3}{13 \cdot 7} - 1 =\]
\[= \frac{1}{2} - 1 = - \frac{1}{2}\ \]